The Phenomenon of Sincerity in Interpersonal Communication (Based on the English Language) - Sivenkova, Maria (Respectus Philologicus, 2005)
Sincerity as a parameter of interpersonal communication can be researched from different perspectives: cognitive, cross-cultural, pragmalinguistic, etc. The first two approaches are exemplified in the paper based on the English noun sincerity and the Russian isla-ennost and several related concepts. Considering the latter perspective, the article focuses on sincerethematisation in dialogue. The article proposes a multidimensional taxonomy of the contexts of sincerity based on the following grounds: the relevant parameter of sincerity (illocutionary, qualitative, quantitative ); illocutionary characteristics of the communicative move (sincerity thematisation in the form of statements, questions, directives); the position of the respective communicative move in dialogue (prospective and retrospective contexts of sincerity ); the position of the component explicating sincerity in the communicative move (distant and contact sincerity thematisation); participants of the communicative interaction (thematisation of the speaker’s / hearer’s sincerity); additional pragmatic aims of the speaker (altruistic and self-serving contexts). These classifications fall into three main classes: dialogical, syntactical and semantic-pragmatic taxonomies of the contexts of sincerity.
Keywords: sincerity; interpersonal communication; communicative move; speech act; thematisation of sincerity in dialogue; illocutionary parameter of sincerity; qualitative and quantitative parameter of sincerity